Study the effect of foliar spraying with Dionyfer and Azomin on the vegetative growth indicators of the leaves of Henna plant( Lawsonia inermis L). - Ahmed Salam Jwar; Mahmoud Shaker Abdel Wahed; Shams Taha Ghani (University of Thi-Qar Journal of agricultural research, 2021)
This study was conducted in the lath house for the College of Agriculture and the Marshes - University of Dhi Qar on the leaves of henna seedlings during the 2020 growing season. The results can be summarized as follows:1- Spraying plants with Dionyfer stimulator at a concentration of (300 ml 100 L-1) led to a significantly excelled in physical traits(plant height (cm), number of secondary branches/plant, the total number of leaves/plant, leaf area (cm2),The weight of the fresh vegetative growth (g), the weight of the dry vegetative growth(g), the weight of the fresh root system (g), the weight of the dry root system (gm), which amounted to (109.08 cm, 6.66 plant branch-1, 246.33 plants, 8.07 cm2 plants -1, 69.91 g, 31.36 g, 31.78 g, 14.14 g) respectively.2- As for the interactions, they had a significant effect on the vegetative growth indicators under study between the Dionyfer stimulator at a concentration (300 ml 100 L-1) and Azomin stimulator at a concentration (350 ml L-1), as all the studied traits excelled within the vegetative growth indicators under study.